WATERING FREQUENCY EFFECT OF FEED CONSUMPTION, ADDED WEIGHT, AND CONVERSION OF ANIMAL FEED PIGS IN LIVESTOCK OWNED DUROC FATHER SAMSURY - Yohanes Ola Lamak, Henny Leondro, Tri Ida Wahyu Kustyorini (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2016)
ABSTRACT The research was conducted on pig farm owned by Mr. Samsuri, Mulyo Village Court, District Dau - Malang starting from May 21 - 17 June 2015. The purpose of this study was to determine the effect of watering frequency of the level of feed intake, feed conversion and weight gain. The materials used include Duroc pigs, cages, feed. 12 heads of pigs at the age of 12-16 weeks and the average weight 27.02 kg. Feed used is the rest of the food stalls. Tools used include: the scale, the hose for watering livestock, the feeding, the wheelbarrow, and room thermometer 1 piece. The research method uses four treatments and three replications. Each treatment consists of three pigs. P0 treatment without watering, watering twice P1, P2 watering three times, and four times P3 watering. Feed given a limited basis. The data obtained in the study were analyzed using analysis of variance RAL, if there is the influence followed by LSD test. Based on the results kosumsi highest feed on P3 (1782.14 g), and the lowest P0 (1340.47 grams). The highest body weight gain contained in P3 (332 grams), and the lowest in P1 (225.66 grams). Feed conversion is highest in P1 (6.86), and the lowest P3 (5.36). Based on the results of the study concluded that the frequency of watering Duroc pigs are very significant (P 0.05). Advice can be given regarding the outcome of this study is the frequency of watering can be done as often as possible to increase consumption. Keywords: Duroc pigs, consumption, conversion